KAJIAN PENYEMBUHAN PENDETA KORBAN KDRT DI KLASIS KOTA KUPANG - Mesakh Abia Pello Dethan; Isakh A. Hendrik; Ira Mangililo; Max Leunupun; Ade Damayanti (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2023)
This research is a type of field research, while the approach used is descriptive-qualitative, researchers use interview, observation and documentation methods in collecting data. The purpose of this research is to find out how opportunities for pastors who are victims of domestic violence to do self-healing. It is hoped that achieving this goal can be useful for pastors who experience domestic violence to imitate the behavior taken by victims who have succeeded in self-healing. Research results have shown that pastors who experience domestic violence can be strong in facing problems and able to heal themselves. All respondents acknowledged that the internalization of Christian values contained in the testimonies of the OT and NT was the determining factor in them being able to recover from the pressure of domestic violence issues. In addition, the fact shows that the ability of the respondents in pastoral care to solve the problem of domestic violence that is applied to the congregation who has experienced domestic violence can also be applied to themselves so that they can help their recovery quickly.